1905 Ind. Acts 688 - (:unkn) unknown (My University, 1905)
Toy Pistols, § 451: Prohibited the manufacture, sale, exposing for sale, or giving away as a prize, or reward, any toy pistol or other device for the purpose of exploding caps or wafers containing fulminates or other explosive compounds. Violators guilty of a misdemeanor, fined not less than ten nor more than fifty dollars, or imprisoned in county jail not less than ten days nor more than twenty days.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES